SENSITIVITY OF HOUSEHOLDS CONSUMPTION DEFLATOR TO CHANGES IN PRICES OF IMPORTED AGRICULTURAL PRODUCTS - Gorzałczyński, Artur; Przybyliński, Michał (Acta Scientiarum Polonorum. Oeconomia, 2018)
The aim of the article is to assess the sensitivity of the deflator of households consumption to changes in prices of imported agricultural products. In addition to assessing the scale of this sensitivity, its changes in time and spatial diversification were tracked. The research used the input – output price model. It is a macroeconomic model based on the cost formula, and therefore price sensitivity is described through the prism of flows of intermediate products, ignoring adjustment mechanisms. The statistical material for the period 2000–2014 was taken from world input – output database (WIOD) covering information about 43 countries of the world. The analysis carried out shows that changes in world prices of agricultural products have a rather small impact on the purchasing power of households. The observed changes in time are varied, however, the upward trend prevails. The results confirm the thesis that the sensitivity to price impulses flowing from abroad decreases along with the size of the country. Very clearly, especially in European countries, a breakdown in 2009 can be noticed, resulting from the financial crisis, which also moved to the real sphere.